Factors Influencing Employee Performance and Loyalty at Kasih Hospital, Denpasar - Komang Rhismala Oktaryanti Wulan; Sentot Imam Suprapto; Agusta Dian Ellina (Health and Technology Journal (HTechJ), 2025)
Human resources (HR) is a key factor in organizational success, including that of private hospitals. Kasih Ibu General Hospital in Denpasar faces high healthcare worker turnover and low BOR (68%), necessitating effective HR management. Factors such as leadership style, compensation, work motivation, job satisfaction, work culture, and work environment are suspected to influence employee performance and loyalty. This study aims to analyze Factors Influencing Employee Performance and Loyalty at Kasih Hospital, Denpasar. This study used a correlational approach with a cross-sectional design. The population included 125 employees, all of whom were sampled. Data were collected through a valid and reliable five-point Likert scale questionnaire. The independent variables included compensation, work motivation, leadership style, job satisfaction, and work culture. The moderating variable was the work environment, and the dependent variables were employee performance and healthcare worker loyalty. The analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) using SPSS. Compensation, work motivation, leadership style, job satisfaction, and work culture significantly influenced performance. Loyalty, compensation, leadership style, and work culture were found to be significant, while work motivation and job satisfaction were not. The work environment strengthens the relationship between job satisfaction and loyalty, but not the relationship between leadership style and performance. The most significant factor influencing performance is leadership style, while work culture is the primary factor affecting loyalty. Leadership, compensation, work motivation, job satisfaction, and work culture all play a role in enhancing employee performance. Additionally, healthcare worker loyalty is influenced by compensation, leadership, and work culture.